Images of Polish Cities in Promotional Visual and Verbal Symbols. What Logos and Slogans Say about Desired Image of the Polish Cities? - Adamus-Matuszyńska, Anna; Dzik, Piotr (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2022)
Advertising is one of the commonly visible elements of the urban landscape (real and virtual). It also does not require proof that advertisements of cities as such are also part of their “cityscape.” Since at least the nineteenth century, cities have advertised themselves as attractive places to live, visit, or do business. Therefore, the following research question can be asked: How do Polish cities present themselves in advertisements one can find in the landscape? The study assumes that each advertisement should clearly identify the sender and indicate its specific characteristics, distinguishing itself from its competitors. Polish cities began to use logos and slogans as a mechanism of description and distinction after 1990, when socioeconomic changes started. There are quite a few studies on this activity, but most of them are single case studies. Therefore, the authors decided to examine a relatively large sample of Polish cities, which allows for statistical analysis. Analysis of the logo and slogan content allows the authors to examine the desired image or the projected identity of Polish cities. The methods were chosen because they admit qualitative and quantitative analysis, especially when there is a sufficiently large sample. Therefore, the survey covered all towns and cities with more than 20,000 inhabitants in Poland. There are 218 such towns in total. The analysis was carried out in the first half of 2021. In conclusion, the authors find that the advertising of Polish cities is embedded in the past, promotes resources (substance), sometimes geographical location, but rarely refers to famous characters and human potential. And such a picture of these cities one may find on outdoor advertisements, which sometimes produce dissonance when accompanying modern buildings or new transport solutions in the city.